Pituitary tumor diagnosis using gadolinium-enhanced magnetic resonance imaging in a dog with hyperadrenocorticism. A case report - Hernández, Carlos; Alzate G., Gildardo J. (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary Cushing's disease is a common endocrine disorder of dogs, caused by persistent high concentration of cortisol in circulating blood. Almost eighty five percent of the cases of spontaneous hyperadrenocorticism in dogs are the result of a functional pituitary tumor or hyperplasia. Advanced imaging techniques like computed tomography (CT) or magnetic resonance imaging (MRI) are the best means to obtain a diagnosis of a pituitary tumor in dogs with pituitary-dependent hyperadrenocorticism (PDH). Moreover these imaging techniques are required to asses the size and location of the pituitary tumor when planning surgical removal of the tumor mass or of the complete pituitary gland. In Colombia, the use of these imaging techniques is very limited in the small animal practice, but it has recently become available for veterinary patients thanks to agreements with human clinical institutions. This report describes the case of an eleven year-old golden retriever with PDH as a result of a functional pituitary tumor, visualized by magnetic resonance imaging using gadolinium as contrast agent. Resumen La enfermedad de Cushing es un trastorno endocrino común en perros causado por altas y persistentes concentraciones de cortisol en sangre. Casi el 85% de los casos de hiperadrenocorticismo espontáneo en perros son el resultado de un tumor funcional o una hiperplasia pituitaria. Las técnicas avanzadas de diagnóstico por imagen como la tomografía axial computarizada (TAC) o la resonancia magnética (RM) son los mejores métodos para obtener el diagnóstico de un tumor pituitario en pacientes con hiperadrenocorticismo dependiente de la hipófisis (PDH). Además estas técnicas son necesarias para determinar el tamaño y localización del tumor pituitario cuando se planea la extracción quirúrgica de la masa o la hipófisis completa. En nuestro país, el uso de estas técnicas por imagen está muy restringido en la práctica de pequeñas especies, sin embargo recientemente han estado disponibles para los pacientes veterinarios gracias al uso de instituciones médicas humanas. En este reporte se describe el caso de un Golden retriever de 11 años con PDH como resultado de un tumor funcional pituitario, que fue visualizado usando RM utilizando gadolinio como medio de contraste.